A study on Systematic review of Gamification in Education Sector - Pathak, Ms. Shipra; Aggarwal, Dr. Shalini; Yashika, Ms. (The journal of contemporary issues in business and government, 2021)
Game based learning has gained importance recently. Because of its playful nature it is able to motivate and attract students. Explaining the concept through games is a technique to make students learn better. Students have vide experience with respect to master, understanding , enjoyment and motivation [1]. During 2000 the main form of E learning was different as compared to it in present form. Use of DVDs, CD RoM, floppy disk was used. With advancement in technology it has moved to use through mobile, laptop and other social media websites that includes Facebook, whatsapps, Amazon and many more [2].